KOMUNITARIANISME: Konsep Tentang Bermasyarakat - Daeli, Doniman Gavenoreli; Kelana, Muhamad Rifaldi; Purnama, Kharisma Candra; Wiracitra, Bambang; Sinaga, Jonan Bungaran Basuki (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Communitarianism is the idea that human identities are largely shaped by different kinds of constitutive communities (or social relations) and that this conception of human nature should inform our moral and political judgments as well as policies and institutions. We live most of our lives in communities, similar to lions who live in social groups rather than individualistic tigers who live alone most of the time. Those communities shape, and ought to shape, our moral and political judgments and we have a strong obligation to support and nourish the particular communities that provide meaning for our lives, without which we’d be disoriented, deeply lonely, and incapable of informed moral and political judgment.